2021
DOI: 10.1080/21655979.2021.1917227
|View full text |Cite
|
Sign up to set email alerts
|

REDD1 (regulated in development and DNA damage-1)/autophagy inhibition ameliorates fine particulate matter (PM2.5) -induced inflammation and apoptosis in BEAS-2B cells

Abstract: This study aimed to investigate the implication of REDD1 on airborne particle matter-induced lung injury and whether it is mediated through autophagy. Cell viability in BEAS-2B cells induced by PM2.5 was measured by CCK-8. RT-qPCR and Western blot were performed to determine mRNA and protein levels of REDD1 as well as inflammatory cytokines, respectively. Cell apoptosis was observed with TUNEL staining. The expression of autophagy-related genes was detected by Western blot. Autophagy level was observed with GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The cell death shown in RTEC injury, which is an excellent feature of DN, is characterized by apoptosis. Accumulating evidence demonstrates that the inhibited REDD1 expression not only induced apoptosis of human umbilical vein endothelial cells after exposure to LPS, but also noticeably alleviated PM2.5-induced BEAS-2B cell apoptosis [ 21 , 34 ]. A study reported that REDD1 overexpression is sufficient to promote neuronal apoptosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell death shown in RTEC injury, which is an excellent feature of DN, is characterized by apoptosis. Accumulating evidence demonstrates that the inhibited REDD1 expression not only induced apoptosis of human umbilical vein endothelial cells after exposure to LPS, but also noticeably alleviated PM2.5-induced BEAS-2B cell apoptosis [ 21 , 34 ]. A study reported that REDD1 overexpression is sufficient to promote neuronal apoptosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…After being fixed in 4% paraformaldehyde for 15 min, cell apoptosis was tested in accordance with the instructions of a TUNEL Apoptosis Detection kit (Beyotime, Shanghai, China) under the operation guidelines provided by the manufacturer [ 28 ]. After being centrifuged and washed for twice with phosphate buffer saline (PBS), cells were fixed with 4% paraformaldehyde for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Different concentrations of resveratrol solution were added to the cell culture medium in the dish to keep a final concentration of DMSO less than 0.1% in the culture medium. Then, the cytotoxicity test in the mHSCs after different concentrations of PM 2.5 (0, 1, 5, 10, 25, 50, 100, 200, 250, 500 µg/mL) and RES (0, 1, 2.5, 5, 10, 20, 50, 100 and 200 µmol/mL) was performed according to the previous study [17] and the instructions of the CCK8 assay kit (Beyotime Biotechnology, Shanghai, China). In brief, we prepared a mixture solution by combining cell culture medium and CCK-8 solution at a volume ratio of 10:1.…”
Section: Assessment Of Cytotoxicitymentioning
confidence: 99%